INNOVATION CAPABILITY AND ADAPTIVE COMPETITIVENESS OF MSMEs:AN INTEGRATIVE FRAMEWORK FOR SUSTAINABLE BUSINESS GROWTH - Nida Garnida Fitrianti; Raden Roro Fatmasari (Organisasi Kreatif Indonesia Emas, 2024)
Background: MSMEs face persistent pressure to adapt products, processes, market channels, and organizational routines under resource constraints. Innovation capability offers a useful lens for explaining why some enterprises convert limited resources and external knowledge into sustained adaptation while others remain vulnerable to environmental change. Aims: This article develops an integrative conceptual framework linking innovation capability, absorptive capacity, dynamic capabilities, organizational learning, networks, and adaptive competitiveness in MSMEs. Research Method: The paper uses an integrative conceptual review of established literature published before the July 2024 issue placement. It does not claim primary survey, interview, experimental, or statistical data. Results and Conclusion: The synthesis identifies six mutually reinforcing capabilities: opportunity sensing, knowledge acquisition and assimilation, resource recombination, experimentation, commercialization, and learning-based reconfiguration. Innovation strengthens adaptive competitiveness when MSMEs connect internal routines with customers, suppliers, universities, communities, and other ecosystem actors while maintaining disciplined evaluation of cost and value. Contribution: The article proposes an MSME Innovation Capability Cycle, practical capability indicators, and research propositions that can guide future empirical studies and enterprise-development programs.